Phase I/II trial of concurrent extracranial palliative radiation therapy with Dabrafenib and Trametinib in metastatic BRAF V600E/K mutation-positive cutaneous Melanoma. (September 2021) - Wang, Wei; Smith, Jessica Louise; Carlino, Matteo Salvatore; Burmeister, Bryan; Pinkham, Mark Blayne; Fogarty, Gerald Blaise; Christie, David Robert Harry; Estall, Vanessa; Shackleton, Mark; Clements, Arthur; Wolfe, Rory; Thao, Le Thi Phuong; et al.
Highlights: Our study investigated the safety and tolerability of palliative radiation therapy (RT) with concurrent Dabrafenib and Trametinib in patients with metastatic BRAF mutant melanoma, and we found that none of the patients enrolled in this study experienced grade 3 or 4 RT related toxicities. We suggest that Dabrafenib and Trametinib may be safely used concurrently with common palliative RT doses to extracranial sites. Abstract: Background: Concurrent treatment with BRAF inhibitors and palliative radiation therapy (RT) could be associated with increased toxicity, especially skin toxicity. Current Eastern Cooperative Oncology Group (ECOG) consensus guideline recommend ceasing BRAF inhibitors during RT. There is a lack of data regarding concurrent RT with combined BRAF and MEK inhibitors. This single-arm phase I/II trial was designed to assess the safety and tolerability of palliative RT with concurrent Dabrafenib and Trametinib in patients with BRAF-mutant metastatic melanoma. Materials and methods: Patients received Dabrafenib and Trametinib before and during palliative RT to soft tissue, nodal or bony metastases. The RT dose was escalated stepwise during the study period. Toxicity data including clinical photographs of the irradiated area was collected for up to 12 months following completion of RT. Results: Between June 2016 to October 2019, ten patients were enrolled before the study was stopped early due to low accrual rate. Six patients were treated at level 1 (20 Gy in 5 fractions, any location) and 4 patients at level 2a (30 Gy in 10 fractions with no abdominal viscera exposed). All alive patients completed one year of post-RT follow-up. Of the 82 adverse events (AEs) documented, the majority (90%) were grade 1 and 2. Eight grade 3 events (10%) occurred in five patients, only one was treatment-related (grade 3 fever due to Dabrafenib and Trametinib). No patients experienced grade 3 or 4 RT related toxicities, including skin toxicities. One serious AE was documented in relation to a grade 3 fever due to Dabrafenib and Trametinib requiring hospitalisation. Conclusions: The lack of grade 3 and 4 RT-related toxicities in our study suggests that Dabrafenib and Trametinib may be continued concurrently during fractionated non-visceral palliative RT to extracranial sites.